Preparation of thick soup from cassava (Manihot esculenta) - Alim, Vivian Rose Doce (2009.)
This study was conducted to develop a ready food from cassava.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Cassava; Manihot esculenta